Changes in tonsillolith characteristics detected in a follow-up CT study - Kouhei Yamashita; Masafumi Oda; Tatsurou Tanaka; Ikuko Nishida; Nao Wakasugi-Sato; Shinobu Matsumoto-Takeda; Manabu Habu; Teppei Sago; Osamu Takahashi; Hiroki Tsurushima; Shiro Tabe; Taishi Otani; et al. (BMC, 2021)
Abstract Background Tonsilloliths are related clinically to halitosis and tonsillar abscess. However, the dynamics of tonsilloliths over time are unknown. The aim of the study was to evaluate change in the characteristics of tonsilloliths in a time-dependent fashion by follow-up computed tomography (CT). Methods Tonsilloliths were analyzed in 326 CT scan pair sets of initial and at least two follow-up CT examinations of patients with whole palatine tonsils and various diseases of the oral and maxillofacial regions. Results Over the follow-up period, 12.1% of tonsilloliths disappeared. Approximately 26.1% of tonsilloliths changed in size during follow-up, mostly increasing in size. In tonsilloliths that showed enlargement, the mean (± standard deviation) growth rate was 0.61 ± 0.41 mm per year. Approximately 37.3% of tonsilloliths changed position during the follow-up period; of these, movement was toward the respiratory tract in 92% at a mean rate of − 1.38 ± 1.59 mm per year. The calcification levels of almost all tonsilloliths showed dynamic change: HU number increased in 84.3% and decreased in 12.7% of tonsilloliths over the follow-up period. The mean rate of HU increase was 63.8 ± 96.3 HU/year, and the mean rate of HU decrease was − 38.4 ± 66.8 HU/year. Conclusions The calcification levels of all tonsilloliths showed dynamic fluctuation, and a tendency for excretion of tonsilloliths from the body. Their dynamics over time suggest that tonsilloliths may be in a permanently active phase which functions to remove foreign matter.